Synergistic regulation mechanism of nitrogen and potassium coupling on sugarcane yield and soil quality in karst areas - Zhong, Ning; Cai, Qiuliang; Huang, Jinsheng (Frontiers in Plant Science, 2025)
To address the conflict between soil degradation and sugarcane productivity in South China karst regions, this study investigated the coordinated regulatory effects of fertilization practices on sugarcane yield, soil enzymatic activities, and ecological stoichiometry through nitrogen-potassium coupling experiments, establishing a theoretical framework for precision nutrient management. A field experiment evaluated the soil enzymatic activities, nutrient concentrations, ecological stoichiometry indices, and sugarcane productivity across eight nitrogen-potassium application ratios (N0K0 to N3K2). The direct and indirect effects of fertilization measures were quantified using structural equation model (SEM), grey relational analysis and path analysis. The results showed that the high nitrogen and high potassium treatment (N3K2) achieved maximum sugarcane yield (91.05 t ha-1), representing a 55.25% increase over the control, but leading to soil acidification (pH 4.57). Optimal nitrogen use efficiency (38.47%) occurred under the low nitrogen and high potassium treatment (N1K2), exceeding conventional fertilization by 21.41%. Path analysis revealed that urease exerted the strongest direct yield effect (1.977), while total potassium demonstrated the highest grey correlation degree (0.911). The medium nitrogen and high potassium treatment (N2K2) exhibited optimal soil fertility (IFI = 0.57) with significantly higher total base ions (0.48 Cmol kg-1) compared to other treatments. The ecological stoichiometric characteristics showed that the soil in the study area was in the state of nitrogen limitation (nitrogen-phosphorus ratio = 1.89) and phosphorus efficiency (carbon-nitrogen ratio = 9.56-23.25). Structural equation modeling revealed nutrient cycling influenced sugarcane yield through enzymatic regulation (total effect = 0.702). This study established an acid soil ternary regulation framework integrating enzyme activity, nutrient cycling, and stoichiometric balance, while recommending the optimization scheme of nitrogen-potassium ratio (N:K2O ≈ 1:1.5) for southern sugarcane cultivation. The ammonium nitrogen activation coefficient (> 1.5%) and carbon-phosphorus ratio (< 25%) were identified as pivotal fertility monitoring parameters, offering theoretical foundations for precision fertilization and sustainable soil management in karst areas.